RADIATION DOSE OF THE EYE LENS IN CT EXAMINATIONS OF THE BRAIN IN CLINICAL PRACTICE—THE EFFECT OF RADIOGRAPHER TRAINING TO OPTIMISE GANTRY TILT AND SCAN LENGTH. Issue 5 (23rd January 2023) - Tarkiainen, Jeremias; Nadhum, Miia; Heikkilä, Annele; Rinta-Kiikka, Irina; Joutsen, Atte
Abstract: Lenses are always exposed to radiation in brain computed tomography (CT) scans. However, the lens dose can be reduced by excluding lens from scanning area by optimising gantry tilt and scan length. The object of this study is to retrospectively analyse if the optimisation by gantry tilt and scan length have been adequate in the CT scan of the brain, and to prospectively analyse the effect of radiographer training to the quality of the CT examinations. This study was conducted in two parts. In all, 329 brain CTs performed in the Tampere University Hospital from 2017 to 2019 were revised retrospectively. The prospective part included 51 brain CT studies conducted in October 2021. Dose to the eye of the lens was modelled using CT-Expo using zero-degree beam angle and scan lengths to expose the lens either to the primary or scattered radiation. Non-zero gantry tilt had been used in a large proportion of the CT examinations in the retrospective setting, 84.8%. However, the lenses were successfully excluded from the scan area in only 1.8% of the examinations. In the prospective part, the gantry tilt was used in 98% of the studies and the proportion of successful examinations rose from 1.8 to 11.8%. The lens dose decreased significantly when the eyes were excluded from the imaging area. The modelled lens dose in the large retrospective part was 25.9 mGy (17.8–49.2 mGy) when the eyes were included and 1.5 mGy (0.4–1.9 mGy) when the eyes were excluded. The lens dose was similar in the small prospective part. Despite the gantry tilt is widely used, unnecessary lens irradiation occurs extensively because of suboptimal gantry tilt and scan length. The training of radiographers reduces the radiation exposure to the lens by more optimal gantry tilt and scan length.